Democracia, organización y participación de las mujeres: un proceso de construcción de una ciudadanía diferente (2020)
Democracy —in its classical conception as a form of government— has been transforming itself into diverse historical contexts, acquiring senses that account for its performative character. In Venezuela, the social and institutional organization has been impacted by a  form of democracy, constitutionally defined as participatory and leading. Thanks to the leading role played, women have been occupying a fundamental role in the social and political organization, denoting being a device capable of influencing the construction of a citizenship that helps to demolish the political power that until now remains patriarchal.  Hegemonic power relations remain androcentric, even though the women’s revolution makes feminism one of the strongest social movements in the Western world. Now, in relation to the democratic debate, feminist theory manifests itself through two  fundamental positions: a) gaining ground in the face of the universalistic vision of citizenship, or b) making visible the specificity to denounce the patriarchal domination that makes sexual difference a factor of social discrimination. This paper intends to study how these processes have  occurred and how, through leading participation, there has been a substantial transformation in the extension of citizen rights of Venezuelan women.